Visualisation Research into Fuel Spray Propagation - Hubert Kuszewski; Kazimierz Lejda; Zygmunt Szlachta (Communications - Scientific letters of the University of Zilina, 2005)
The results of research into a new construction of a diesel engine multi-hole injector are presented. The injector needle (RSN injector) performs a rotary/swinging movement. During the fuel injection the needle changes the area of atomizing orifices. This design changes the shape of atomized fuel sprays and has impact on their properties. The range of the spray front, the top angle of the spray and the area of the spray projection in a plane perpendicular to the injector axis were analyzed.